Effects of socioeconomic status on children with hearing loss. (January 2019) - Smith, Blake; Zhang, Jessica; Pham, Gina Nhu; Pakanati, Keerthana; Raol, Nikhila; Ongkasuwan, Julina; Anne, Samantha
Abstract: Objective: Health care disparities are noted between different socioeconomic groups; it is crucial to recognize and correct disparities, if present, that extend to children with hearing loss. The objective of the study is to evaluate the effect of socioeconomic status (SES) on access to hearing rehabilitation and speech and language therapy and outcomes in children with hearing loss. Methods: Retrospective Chart Review of children diagnosed with hearing loss at 3 tertiary care academic centers from 2010 to 2012. Two hundred patients were then randomly selected from each institution for analysis. International and self-pay patients were excluded. They were separated into two groups based on SES using insurance coverage as proxy for financial status (private insurance versus Medicaid). Main outcome measures included number of hearing aid evaluations recommended andcompleted, compliance with hearing aids use, diagnosis on speech therapy evaluations, participation in speech therapy, and outcomes noted on the last speech therapy session in patients' medical record at time of study completion. Results: 600 patients were identified by random selection out of total of 3679 patients. 18 were excluded because they were international pay or self-pay. Of 582 patients, 299 (51.4%) had private insurance and 283 (48.6%) had Medicaid. The pure tone average (PTA) at initial diagnosis did not differ between the two populations (left ear p = 0.74, right ear p = 0.68). There was no significant difference in the number of hearing aid evaluations recommended (p = 0.49), hearing aid evaluation completed (p = 0.68), or documented hearing aid compliance (p = 0.68) between the two populations. Similarly, there was no significant difference in the presence of speech delay (p = 0.62), the receipt of speech therapy (p = 0.49), or speech language outcomes between the two groups (p = 0.45). Conclusions: This study suggests that despite lower socioeconomic status, in children with hearing loss, Medicaid allows equivalent access to hearing rehabilitation and speech therapy as their privately insured counterparts and children achieve similar speech and language outcomes.